2014
DOI: 10.1016/j.ygyno.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of invasive circulating tumor cells (iCTCs) in epithelial ovarian cancer

Abstract: Goals: Circulating tumor cells (CTCs) have been introduced as a biomarker in detecting advanced Epithelial Ovarian Cancer (EOC). The goals are to examine the prevalence of the invasive subpopulation of CTCs (iCTCs) in patients at high risk of EOC and to compare this biomarker to serum CA125. Methods: We used a unique Cell Adhesion Matrix (CAM)-based, functional cell enrichment and identification platform to isolate iCTCs from 129 preoperative patients. We confirmed the identity of iCTCs using positive epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 34 publications
5
77
1
Order By: Relevance
“…The same group also investigated the predictive value of CTC levels in a small group of 31 ovarian cancer patients that received standard taxol/carboplatin chemotherapy, where blood specimens were obtained at different time points, before and after surgery and up to 24 months after chemotherapy treatment. Using the same assay [27], they showed a statistically significant association between CTC levels and disease progression [26].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 91%
See 1 more Smart Citation
“…The same group also investigated the predictive value of CTC levels in a small group of 31 ovarian cancer patients that received standard taxol/carboplatin chemotherapy, where blood specimens were obtained at different time points, before and after surgery and up to 24 months after chemotherapy treatment. Using the same assay [27], they showed a statistically significant association between CTC levels and disease progression [26].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 91%
“…They reported that the CAM + CTCs were invasive and their presence significantly correlated with decreased progression-free survival(PFS) (p = 0.042) [34]. The same group evaluated the prognostic significance of CTCs in a group of 129 pre-surgery ovarian cancer patients using the same method for the detection and identification of CTCs and observed statistically significant association between the presence of CTCs and both OS (p = 0.0219) and PFS (p = 0.0024) [27]. The same group also investigated the predictive value of CTC levels in a small group of 31 ovarian cancer patients that received standard taxol/carboplatin chemotherapy, where blood specimens were obtained at different time points, before and after surgery and up to 24 months after chemotherapy treatment.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 97%
“…They also showed that in patients with high-grade adenocarcinoma there was a direct relationship between higher levels of CTCs, more aggressive disease, and higher levels of CA125. Poveda et al [28] also found a direct connection between elevated CTCs and shorter PFS and OS. The study conducted by Poveda was a multicentric phase III study, enrolling 672 patients.…”
Section: Discussionmentioning
confidence: 89%
“…Just like in breast cancer studies, also in ovarian cancer a further characterization of CTCs by use of more marker genes, like PPIC, is pursued (178). A rather new topic in the CTC-field in ovarian cancer is the analysis of invasive CTCs (iCTCs), as it was shown that iCTCs are better correlated to progressionfree and overall survival and even more specific than the up to now widely used serum marker CA125 (179). The predictive value of CTC occurrence in ovarian cancer was reconfirmed in 2015 in a study of Zeng et al (180), who was able to demonstrate, that patients with CTCs in the peripheral blood had a shorter DFS and OAS than patients without CTCs in their blood.…”
Section: Recent Developments For Ctc Detection In Ovarian Cancermentioning
confidence: 99%